Fifty years of swan research and conservation by The Wildfowl & Wetlands Trust - Rees, Eileen; Bowler, John (Wildfowl, 1996)
The Wildfowl & Wetlands Trust (WWT) has contributed to the conservation of swan species by establishing refuges for the birds in winter, through its research programmes, and by advising others on site management. This paper describes an increase in the number of migratory swans wintering at Slimbridge, Caerlaverock, the Ouse Washes and Martin Mere following the development of WWT Centres at these sites. The build-up in numbers may be due to changing population levels, and to conditions created by WWT. We describe changes in feeding site selection in the last 50 years, and consider the potential for inter-specific competition between Bewick's and Whooper Swans in areas where the two species co-exist. WWT's long-term studies of individual birds, which have provided detailed insight into the swans' life-cycles, are reviewed. The importance of international collaboration for the effective conservation of migratory waterbirds is again emphasised.